BRAC Education Program (BEP): progress report, January - June 2000 - BRAC (© BRAC, 2016)
1. Introduction 2. NFPE grades IV and V 3. Plan and achievement of staff training 4. Education development unit 5. RED research studies 6. Others activities of BEP 7. Financial summary and details.